Biomechanical evaluation of anterior lumbar interbody fusion with various fixation options: Finite element analysis of static and vibration conditions. (April 2021) - Shen, Hangkai; Chen, Yuru; Liao, Zhenhua; Liu, Weiqiang
Abstract: Background: Anterior lumbar interbody fusion combined with supplementary fixation has been widely used to treat lumbar diseases. However, few studies have investigated the influence of fixation options on facet joint force and cage subsidence. The aim of this study was to explore the biomechanical performance of anterior lumbar interbody fusion with various fixation options under both static and vertical vibration loading conditions. Methods: A previously validated finite element model of the intact L1–5 lumbar spine was employed to compare five conditions: (1) Intact; (2) Fusion alone; (3) Fusion combined with anterior lumbar plate; (4) Fusion combined with Coflex-F fixation; (5) Fusion combined with bilateral pedicle screw fixation. The models were analyzed under static and vertical vibration loading conditions respectively. Findings: Bilateral pedicle screws provided highest stability at surgical level. Applying supplementary fixation diminished the dynamic responses of lumbar spine. Compared with anterior lumbar plate and Coflex-F device, bilateral pedicle screws decreased the stress responses of the endplates and cage under both static and vibration conditions, while increased the facet joint force at adjacent levels. As for comparison between Coflex-F device and anterior lumbar plate, results showed a similarity in biomechanical performance under static loading, and a slightly higher dynamic response of the latter under vertical vibration. Interpretation: The biomechanical performance of lumbar spine was significantly influenced by the variation of fixations under both static and vibration conditions. Bilateral pedicle screws showed advantages in stabilizing surgical segment and relieving cage subsidence, but may increase the facet joint force at adjacent levels. Highlights: The application of supplementary fixation decreased the dynamic responses of lumbar spine. Bilateral pedicle screws may stabilize surgical segment and relieve cage subsidence. Bilateral pedicle screws may increase the facet joint force at adjacent levels. Coflex-F and anterior lumbar plate showed similar performance under static loading. Compared with Coflex-F, anterior lumbar plate slightly increased the dynamic responses.